A escrita como túmulo e memorial em Bernardo Kucinski - Ricardo Augusto Garro Silva (2020)
The thesis A escrita como túmulo e memorial em Bernardo Kucinski has as fundamental objective to study some forms of expression of the testimony of the resistance to the Brazilian civil-military dictatorship, in addition to the collective symbolization of memory, from the analysis of K. – Relato de uma busca, by Bernardo Kucinski. In this novel, we have the individual memory elaborated by fiction, through mourning figures, both with regard to its impossibility, symbolized in the melancholy exposed in the trajectory of the father, the character K., as well as in the attempt to overcome, through writing, by the son. In the tension between these two paths, the text stages the father's clashes with the State, as well as the transmission of his memory, by the son, through fiction. In this crossing of memories and forgetfulness, demands from the past become present. Thus, the novel establishes a commitment and the continuation of an attempt at political resistance based on identity marks. These, fictionally elaborated, affirm themselves from what can be defined as an attempt to find a way out and an understanding for the events that afflicted the author's family, making pertinent to their work what Gilles Deleuze and Félix Guattari pointed out about of Kafka's work, having as reference Carta ao pai. For them, Kafka's literature, as an expression, may become a possibility and an escape line that establishes a different order. For that, the authors start from the idea of an identity slip uniting father and son around the traumas and tragedies that afflicted the Central European Jewish community in the early 20th century, which serves to analyze not only Carta ao pai, but also all of Kafka's work, from a perspective that links the individual journeys of father and son to the collective and the social. This perspective may in this thesis, be a way of approaching the work of Bernardo Kucinski, whose main characteristic is the revision of personal history interspersed in the rewriting of historical and political events by fiction.